Write both sides as powers of 16:
![\log_4(2-x)=\log_(16)(13-4x) \implies 16^(\log_4(2-x))=16^{\log_(16)(13-4x)}](https://img.qammunity.org/2021/formulas/mathematics/high-school/dt1z373f8bguzbquqlh95c5chty3x4lx3y.png)
Since 16 = 4², we can rearrange the left side to get
![16^(\log_4(2-x))=(4^2)^(\log_4(2-x))=4^(2\log_4(2-x))=4^(\log_4(2-x)^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9c07k3884dx8ohjoxkfdwpoatatdxha65g.png)
Then, recalling that
, we have
![4^(\log_4(2-x)^2)=16^{\log_(16)(13-4x)}\implies(2-x)^2=13-4x](https://img.qammunity.org/2021/formulas/mathematics/high-school/50twrotazt7plbljncblgyv8kwph4hd0j1.png)
Now solve for x :
![(2-x)^2=13-4x](https://img.qammunity.org/2021/formulas/mathematics/high-school/8ahwk0yatar64t0r0u3ib3d1wlt1wrc4nn.png)
![4-4x+x^2=13-4x](https://img.qammunity.org/2021/formulas/mathematics/high-school/dffivgtdnd9c1g4dvzzmutrp0gs8gqnlwh.png)
![x^2-9=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mp8apvi7kr3lcy9aenr4iy58ve17epcjfm.png)
![(x+3)(x-3)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/zwri2icuzyfkv1ra2ixv3yrsfxwew283zl.png)
![\implies x=-3\text{ or }x=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/mtkf6l1ila2dadebdj69mth8k4iy3zcun6.png)
Notice that if x = 3, then log₄(2 - x) = log₄(-1) is undefined, so we throw out this solution. We don't run into this problem with x = -3, so that's the only (real) solution.